Are there differences in the characteristics of patients who respond to gemcitabine plus cisplatin chemotherapy and those who respond to pembrolizumab therapy for metastatic urothelial carcinoma? Multicenter retrospective study. (2nd June 2022) - Shindo, Tetsuya; Maehana, Takeshi; Tanaka, Toshiaki; Hashimoto, Kohei; Kobayashi, Ko; Takahashi, Atsushi; Hotta, Hiroshi; Kunishima, Yasuharu; Taguchi, Keisuke; Tachiki, Hitoshi; Ito, Naoki; Matsukawa, Masanori; et al.
Abstract : Objectives: To evaluate factors to predict overall survival of metastatic urothelial carcinoma patients treated with gemcitabine plus cisplatin chemotherapy or pembrolizumab therapy. Methods: We retrospectively evaluated two metastatic urothelial carcinoma cohorts treated with (i) gemcitabine plus cisplatin or (ii) pembrolizumab. The gemcitabine plus cisplatin cohort was treated from December 2005 through December 2014 while the pembrolizumab cohort was treated from January 2018 through December 2020. Using multivariate analyses, we evaluated the risk factors for overall survival in each cohort and compared them. None of the gemcitabine plus cisplatin cohort patients were treated with pembrolizumab. All patients in the pembrolizumab cohort were treated with prior platinum‐based chemotherapy. Results: There were 184 patients in the gemcitabine plus cisplatin cohort and 91 in the pembrolizumab cohort. The mean follow‐up periods were 714 and 284 days, respectively. In multivariate analysis, the risk factors for overall survival in the gemcitabine plus cisplatin cohort were liver metastasis, worse Eastern Cooperative Oncology Group performance status (1 or more), no primary site resection, and a high prognostic index (1 or more). In the pembrolizumab cohort, liver metastasis, bone metastasis, and worse Eastern Cooperative Oncology Group‐performance status (1 or more), and high prognostic index (1 or more) were the risk factors for overall survival. In the pembrolizumab cohort, patients with a complete response or partial response during prior platinum‐based chemotherapy had better overall survival with the following pembrolizumab treatment than those with stable or progressive disease ( P = 0.004). Conclusions: Considering the similarity of these risk factors in two sequential treatments, it may be possible to predict the response to pembrolizumab according to the response to prior chemotherapy.